2019
DOI: 10.1111/risa.13404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Dose–Response Relationship Between Folate Exposure and Cognitive Impairment: Synthesizing Data from Documented Studies

Abstract: The dose–response relationship between folate levels and cognitive impairment among individuals with vitamin B12 deficiency is an essential component of a risk‐benefit analysis approach to regulatory and policy recommendations regarding folic acid fortification. Epidemiological studies provide data that are potentially useful for addressing this research question, but the lack of analysis and reporting of data in a manner suitable for dose–response purposes hinders the application of the traditional evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…We found a trend for better memory performance with higher folate, but worse attention with elevated folate in both men and women. These results are similar to the previously reported finding of a J-shaped dose-response relationship between folate exposure and risk of cognitive impairment for those with vitamin B12 deficiency (26). This may reflect the fact that high folate levels can mask B12 deficiency due to their shared metabolic reactions.…”
Section: Discussionsupporting
confidence: 91%
“…We found a trend for better memory performance with higher folate, but worse attention with elevated folate in both men and women. These results are similar to the previously reported finding of a J-shaped dose-response relationship between folate exposure and risk of cognitive impairment for those with vitamin B12 deficiency (26). This may reflect the fact that high folate levels can mask B12 deficiency due to their shared metabolic reactions.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been found in another meta-analysis, which indicated a dose-response relationship between folic acid and the risk of cognitive impairment in older adults with vitamin B-12 deficiency. The study suggested a “J shape” relationship between serum folate concentration and cognitive impairment [ 48 ]. The suggested mechanism behind this relationship is that elevated folate might mask vitamin B-12 deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested mechanism behind this relationship is that elevated folate might mask vitamin B-12 deficiency. Epidemiological studies have shown that individuals with low serum vitamin B-12 in combination with high folate present a higher risk of cognitive impairment compared to those with normal serum folate, especially in the elderly population due to lower absorption of vitamin B-12 [ 29 , 48 ]. It has been estimated that folic acid fortification might be associated with an increase in the risk of cognitive impairment in up to 4% of older adults in the US [ 29 ].…”
Section: Resultsmentioning
confidence: 99%